Nietzsche and transhumanism : precursor or enemy? - Tuncel, Yunus (Nietzsche Now Series, 2017)
This essay collection deals with the question of whether Nietzsche can be seen as a precursor of transhumanism or not. Debates on the topic have existed for some years, particularly in the Journal of Evolution and Technology and The Agonist. This book combines existing papers, from these journals, with new material, to highlight some of the important issues surrounding this argument. The collection addresses a variety of issues to show whether or not there is a close connection between transhumanist concerns for progress and technology and Nietzsche's ideas.